Monitoring institutions in health care markets: Experimental evidence - Silvia Angerer; Daniela Glätzle-Rützler; Christian Waibel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
This paper investigates the impact of monitoring institutions on market outcomes in health care. Health care markets are characterized by asymmetric information. Physicians have an information advantage over patients with respect to the appropriate treatment for the patient and may exploit this informational advantage by over- and underprovision as well as by overcharging. We introduce two types of costly monitoring, endogenous and exogenous. When monitoring detects misbehavior, physicians have to pay a fine. Endogenous monitoring can be requested by patients, whereas exogenous monitoring is performed randomly by a third party. We present a toy model that enables us to derive hypotheses and to test them in a laboratory experiment. Our results show that introducing endogenous monitoring reduces the level of undertreatment and overcharging. Even under high monitoring costs, the threat of patient monitoring is sufficient to discipline physicians. Introducing exogenous monitoring also reduces undertreatment and overcharging when it is performed sufficiently frequently. Market efficiency increases when endogenous monitoring is introduced as well as when exogenous monitoring is implemented with sufficient frequency. Our results, therefore, suggest that monitoring may be a feasible instrument to improve outcomes in health care markets.
Keywords: C91; D82; I11; 330; Credence goods; physician behavior; undertreatment; overtreatment; overcharging; monitoring; laboratory experiment